The histone deacetylase Rpd3/Sin3/Ume6 complex represses an acetate‐inducible isoform of VTH2 in fermenting budding yeast cells. Issue 8 (26th February 2015) - Stuparevic, Igor; Becker, Emmanuelle; Law, Michael J.; Primig, Michael
Abstract : The tripartite Rpd3/Sin3/Ume6 complex represses meiotic isoforms during mitosis. We asked if it also controls starvation‐induced isoforms. We report that VTH1/VTH2 encode acetate‐inducible isoforms with extended 5′‐regions overlapping antisense long non‐coding RNAs. Rpd3 and Ume6 repress the long isoform of VTH2 during fermentation. Cells metabolising glucose contain Vth2, while the protein is undetectable in acetate and during sporulation. VTH2 is a useful model locus to study mechanisms implicating promoter directionality, lncRNA transcription and post‐transcriptional control of gene expression via 5′‐UTRs. Since mammalian genes encode transcript isoforms and Rpd3 is conserved, our findings are relevant for gene expression in higher eukaryotes. Abstract : VTH1/VTH2 encode acetate‐induced isoforms. The isoforms include an extended 5′‐UTR. The long isoforms overlap antisense long non‐coding RNAs. The VTH2 isoform is repressed in glucose by Rpd3/Ume6. Vth2 protein and VTH2 long isoform levels are negatively correlated.